2009
DOI: 10.1098/rspa.2009.0407
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured bainite

Abstract: An alloy system based on iron is described in which it has been possible to create a high density of interfaces by heat treatment alone. The resulting structure consists of a mixture of slender platelets of bainitic ferrite, just 20-40 nm in thickness, embedded in a matrix of carbon-enriched austenite. The rate at which this structure evolves is slow by conventional standards, but this permits components to be made which are large in all three dimensions, with uniform properties throughout. The fundamental mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
188
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(197 citation statements)
references
References 72 publications
(86 reference statements)
8
188
1
Order By: Relevance
“…In particular, the present results do not provide evidence that these microstructures may exhibit "excessive" austenite stability as suggested in earlier publications [22]. Second, the above results do not confirm the suggested existence of a threshold retained austenite content [17], below which ductile deformation is no longer possible.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…In particular, the present results do not provide evidence that these microstructures may exhibit "excessive" austenite stability as suggested in earlier publications [22]. Second, the above results do not confirm the suggested existence of a threshold retained austenite content [17], below which ductile deformation is no longer possible.…”
Section: Discussioncontrasting
confidence: 54%
“…More recent work, based on measurements of retained austenite content before tensile tests and calculated evolutions, proposed that the stability of retained austenite would influence the material ductility, and indicated that there could be an optimum stability [20]. Data from this same publication were later re-interpreted to propose the existence of a percolation mechanism, whereby ductility was imparted by a percolating network of retained austenite in the matrix of bainitic ferrite, and fracture occurred at an approximately constant volume fraction of 10% retained austenite [17]. Also recently, a model for stress-assisted martensite formation was proposed by the present authors [21] and was found to provide a reasonable agreement with the experiment, though this approach does not provide indication as to the causes of early tensile failures.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…It can be confirmed that the bainitic ferrite lattice have distortion characteristic. In addition, the width of bainitic ferrite lath is nanoscale corresponding with that reported by Bhadeshia [10]. Under p2 process, the bainitic ferrite laths with the small grains are formed naturally during short isothermal time at 450 (such as less 15min) because of limitation of the dislocation cells, leading to high Rockwell hardness value of the sample.…”
Section: Fig 4 the Xrd Patterns Of Samples Experienced Different Tresupporting
confidence: 52%
“…The microstructure of micro/nano-structured bainitic steels consists of nano-structured bainitic ferrites plates (20~65 nm thickness) and carbon-enriched retained austenite films (≥20 vol%), which are formed during low temperature bainitic transformation typically ranging from 200 o C to 300 o C [1][2][3][4][5] . Generally, the presence of retained austenite grains larger than 1 µm in this type of steel is undesirable 6 , because the blocky retained austenite is prone to transform into brittle martensite under the influence of residual stresses or externally applied loads.…”
Section: Introductionmentioning
confidence: 99%